Syntheses and Solid‐State Structures of Bis(dialkylstibanyl)sulfanes and ‐telluranes. Issue 28 (19th September 2013) - Heimann, Stefan; Schulz, Stephan; Bläser, Dieter; Wölper, Christoph
Abstract: Invited for the cover of this issue is the group of Stephan Schulz at the University of Duisburg‐Essen. The cover image illustrates the in situ crystallization technique, which is the thermally induced transformation of polycrystalline (diethylstibanyl)tellurane, (Et2 Sb)2 Te, into a single‐crystalline sample by use of an IR laser, which allows melting and recrystallization of the sample in a N2 cooling steam directly on the diffractometer. The technique provides useful structural information for small molecules and allows a detailed investigation of their intermolecular interactions in the solid state. Abstract : The in situ crystallization technique is a powerful method to obtain single‐crystalline samples of compounds that are typically liquid at ambient conditions... Read more about the story behind the cover in theCover Profile and about the research itself onp. 4909 ff .